Sequential dosing of convalescent COVID-19 plasma with significant temporal clinical improvements in a persistently SARS-COV-2 positive patient. (October 2021) - Mirihagalle, Noupama; Parajuli, Priyanka; Sundareshan, Vidya; Saha, Debadoot; Shah, Arpan; Chua, Francine; Waqar, Sana; Prakash, Vidhya; Tobian, Aaron A.R.; Bloch, Evan M.; Katz, Louis M.; Goel, Ruchika
Abstract: The current global pandemic, SARS-CoV-2 infection, is still extending across the world affecting millions of lives to the date. While new successful vaccines are available with promising outcomes to minimize the spread and to reduce the severity of the disease, optimal therapeutic options still remain elusive. COVID-19 convalescent plasma (CCP) is an investigational treatment option which studies suggesting signals of efficacy and favorable outcomes only for patients treated very early in course of the disease. Benefits of the use of CCP later in the disease remain highly debated and therefore are not common practice. We hereby report a case of severe SARS-CoV-2 infection in a young male patient with prolonged COVID-19 positivity who received repeat doses of CCP treatments later in the disease with temporal clinical improvement. This patient's case highlights the need of further studies evaluating efficacy of repeated dosing of CCP. This also suggests a potential of successful use of CCP later in the disease in selected COVID-19 patients.